Trivariate modelling of the nexus between electricity consumption, urbanization and economic growth in Nigeria: Fresh insights from Maki cointegration and causality tests - Hamisu Sadi Ali; Solomon P. Nathaniel; Gizem Uzuner; Festus Victor Bekun; Samuel A. Sarkodie (African Governance and Development Institute (AGDI), 2020)
In this era of intensive electricity utilization for economic development, the role of urbanization remains inconclusive, especially in developing economies. Here, this study examined the electricity consumption and economic growth nexus in a trivariate framework by incorporating urbanization as an additional variable. Using the recent novel Maki cointegration test, Ng-Perron, Zivot-Andrews, and Kwiatkowski unit root tests along with FMOLS, DOLS and the CCR estimation methods, we relied on an annual frequency data from 1971-2014. Results from FMOLS, DOLS and the CCR regression confirm the electricity consumption-driven economic growth. This is desirable as Nigeria is heavily dependent on energy (electricity) consumption. A unidirectional causality from urbanization to electricity consumption and economic growth was found but the long-run empirical findings revealed urbanization impedes growth - a situation that has policy implications. The study highlights that though urbanization is a good predictor of Nigeria's economic growth, however, the adjustment of the energy portfolio to meet the growing urban demand will curtail the adverse and far-reaching impact of urbanization on the economy.
Keywords: O41; C32; Q43; 330; Economic growth; Electricity consumption; Maki Cointegration; Dynamic Causality; Urbanization